Research Trends in Social and Emotional Learning in Elementary Schools - Nurul Hikmah; Dwi Pratiwi Meisari; Tuti Alawiah; Asri Astria; Intan Fandini; Muhammad Gazali (Inovasi Sekolah Dasar: Jurnal Kajian Pengembangan Pendidikan, 2026)
This study is grounded in the importance of developing Social and Emotional Learning (SEL) in elementary schools as a foundation for building students’ character, empathy, and psychological well-being in facing the challenges of the 21st century. SEL is not only essential for academic success but also plays a crucial role in nurturing emotionally resilient and socially responsible individuals. The purpose of this study is to map the trends and directions of research on SEL at the elementary school level during the period 2020–2025 using bibliometric analysis. The data were collected using the Publish or Perish (PoP) software with Google Scholar as the database source. The data were then analyzed using VOS viewer to identify publication trends, the most highly cited articles, types of research, and thematic relationships among studies. The findings indicate a significant increase in the number of publications, rising from one publication in 2020 to eight publications in 2025. The majority of the studies were literature reviews, accounting for 72% of the total publications. The VOS viewer visualization analysis revealed seven main clusters. Among these seven clusters, two were directly connected to the theme of SEL, highlighting its growing relevance and research focus within the field of elementary education.